Tsunami mortality in Aceh Province, Indonesia - Shannon Doocy; Abdur Rofi; Claire Moodie; Eric Spring; Scott Bradley; Gilbert Burnham; Courtland Robinson
OBJECTIVE: Nine tsunami-affected districts in Aceh, Indonesia, were surveyed between February and August 2005 to characterize tsunami mortality. METHODS: The surveys employed a two-stage cluster methodology with probability proportional to size sampling, and encompassed 1653 tsunami-displaced households with a pre-tsunami population of 10 063 individuals. FINDINGS: Of the original pre-tsunami population, a total of 1642 people, or 17%, were reported as dead or missing in the tsunami. Crude mortality rates in the four survey areas ranged from a high of 23.6% in Aceh Jaya district on the west coast to 5.3% on the east coast. Age-specific mortality rates followed a similar pattern across the four survey areas, with the highest mortality concentrating in the youngest children (aged 0-9 years) and oldest adults (70+). The risk of mortality was significantly greater among females than males; this difference was most pronounced among individuals between ages 10 and 69 years, and diminished among younger and older age groups. CONCLUSION: Mortality risk in the 2004 Asian tsunami varied by geographic location, age and sex. The districts of Aceh Jaya, Banda Aceh and Aceh Besar experienced the greatest mortality. Risk of death was highest among females, and among the oldest and youngest population subgroups. While the full human impact of the Asian tsunami in Aceh Province, in terms of lives lost or damaged, may never be fully measured, the resulting female deficit will likely be the tsunami's most deeply felt and prolonged impact.